What are the determinants of a concerned vision of the future when living with type 2 diabetes? Results from the E3N-AfterDiab study. (September 2019) - Fagherazzi, Guy; Chambraud, Clélia; Dow, Courtney; Mancini, Francesca Romana; Affret, Aurélie; Balkau, Beverley; Magliano, Dianna J; Boutron-Ruault, Marie-Christine; Bonnet, Fabrice
Objectives: Identification of characteristics associated with a negative experience with type 2 diabetes may help to develop novel intervention to improve the outlook of people with the disease. Our aim was to identify determinants of a self-reported concerned vision about the future when living with type 2 diabetes. Methods: In 2630 women with type 2 diabetes from the E3N-AfterDiab study, we used multivariable logistic regression models to derive odds-ratios and 95% confidence intervals. Results: Women with elevated HbA1c levels (OR = 2.42 (1.67–3.49) for ≥7.2% when compared to <6.2%), or treated with injected glucose lowering treatments (OR = 1.37 [1.05–1.81]) had a higher risk of a concerned vision of the future. Age and obesity were associated with a decreased risk. Hypertension, duration of diabetes, smoking, fasting glucose levels, and years of education were not associated with a concerned vision of the future. Discussion: Our findings highlight the importance of both glycemic control and the type of treatment on the perception of the future when living with type 2 diabetes. Subgroups of patients based on these characteristics may receive a specific attention from healthcare professionals to address potential concerns related with diabetes management or the fear of complications.